Application of Cold Water After Physical Activity in Pencak Silat Athletes - Gommo, Saifullah; Jalil, Rasyidah; Saman, Saman; Kahar, Irsan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Physical activity causes an increase in the use of energy or calories by the body. Cold water recovery is to reduce muscle soreness after exercise. The use of cold water for Pencak silat athletes after doing physical activity is very influential with the final result. There are changes in various ways of testing it, such as normality and correlation tests. The goal is that by applying cold water, it can make the pencak silat athletes have a steady pulse and don't get tired quickly. The methods used are experimental, pretest and posttest groups, with 11 sample. The research instrument was carried out after doing physical activity for 1 minute, calculating the pulse for 1 minute after doing physical activity, calculating the pulse was carried out using cold water with 25° C temperature. if the temperature exceeds 25° C then ice cubes are added to the soaking tub until the temperature drops to 25° C. With the normality test Absolute Value = .189 , Positive = .189, Negative = -.189, Sig. 0.200 > 0.05, then the variables are normally distributed and correlation test Correlation Test Sample PreTest = 11 , PreTest Pearson Correlation = 1 PostTest = .971 Meanwhile, PostTest Sample = 11 . PostTest Pearson Correalition = .971 PostTest =1.